Below- or above-elbow immobilization in conservative treatment of distal radius fractures: a systematic review and meta-analysis. Issue 2 (February 2022) - Saka, Natsumi; Hoshika, Shota; Inoue, Madoka; Watanabe, Jun; Banno, Masahiro
Abstract: Introduction: There is no consensus regarding the range of immobilization in the conservative treatment of distal radius fractures (DRFs). Therefore, this systematic review and meta-analysis aimed to compare the clinical outcome of patients with DRFs treated conservatively with below- or above-elbow immobilization. Materials and Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines, two independent reviewers searched MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Clinicaltrials.gov and World Health Organization International Clinical Trials Registry Platform in April 2020; a subsequent update search was conducted in April 2021. We identified all randomised controlled trials comparing two immobilization methods in DRFs. The primary outcome measures were the Disabilities of the Arm, Shoulder and Hand (DASH) or QuickDASH questionnaire scores in the short- and long-term (≤ and >six weeks, respectively) follow-up as well as the treatment failure rate. The secondary outcome measures were radiographic outcome, patient-rated wrist evaluation (PRWE) score, pain score and adverse events. Risk of bias was evaluated using the Cochrane Risk of Bias tool version 2. We used the Grading of Recommendations Assessment, Development and Evaluation approach to evaluate the quality of evidence. Results: The initial search revealed 1, 775 records, and ten studies with 909 participants in total were included. There was no significant difference in DASH score in the short-term follow-up (4.99 lower, 95% confidence interval (CI): 10.45 lower to 0.46 higher; very low certainty) and treatment failure (risk ratio: 0.91, 95% CI: 0.59 to 1.40; low certainty). A clinically irrelevant but significant mean difference (0.83 lower, 95%CI: 1.64 lower to 0.03 lower; low certainty) was found in the DASH score in favour of below-elbow immobilization in the long-term follow-up. The overall risk of bias in DASH scores was high based on the measurement bias. Furthermore, there was no significant difference in secondary outcome measures. Conclusion: This meta-analysis did not demonstrate clinically meaningful difference between below- and above-elbow immobilization in terms of DASH score both in the short- and long-term follow-ups. However, overall certainty of evidence was considered very low, based on the very serious risk of bias, inconsistency and imprecision. Hence, there is a need for further higher quality research. Trial registration number: UMIN000040134 (4/14/2020)